Localizing CLT: A Case Study of a Western-Trained Chinese EFL Teacher at a Chinese University - Yan Gao (Canadian Society for Studies in Education, 2018)
Communicative Language Teaching (CLT) is a second language teaching method prevalent in most English teacher training programs in the Western world. The majority of teacher trainees in CLT-based programs learn English as a foreign language in order to return to their home countries and become English as Foreign Language (EFL) teachers. In many cases, students report that the CLT training environment varies greatly from their experiences as an EFL teacher. This paper investigates the perception of one Western-trained EFL teacher of CLT in China and the strategies she developed to balance communicative methods and traditional Chinese teaching. Realizing the obstacles to implementing CLT in her classroom, Laura developed strategies to adjust to the Chinese context. Using both her learning experience of growing up in China and her educational experience in the United States, Laura was able to navigate conflicting pedagogical backgrounds.